Intellectual Property Rights Protection, Foreign Technology Introduction and FDI- Based on the Provincial-Level Panel Data of China - Dai, Jingchao (Journal of Accounting, Business and Finance Research, 2019)
This article establishes static and dynamic panel models of 30 provinces in China, using a variety of regression models and regression methods to empirically study the impact of China’s intellectual property rights (IPR) protection on FDI. Then verifying whether the impact of intellectual property rights protection on FDI is subject to the level of foreign technology introduction .The innovativeness is constructing a quantitative index system of intellectual property protection of China, which includes intellectual property rights protection legislative level and intellectual property rights protection enforcement level. The research results show that the level of legislation and enforcement of intellectual property rights protection have significant positive impact on China's FDI. For some provinces which urgently need to introduce advanced foreign technology, strengthening intellectual property rights protection will inhibit FDI. Especially the strengthening of the intellectual property rights protection legislative level has a more pronounced inhibitory effect.